Discipline problems in the efl class: is there a cure? (2007)
This article discusses the findings of an action research project carried out to minimize the negative class participation of 10 EFL pre-intermediate students, aged-11-14, in a language school in Rio de Janeiro, Brazil. First, some theoretical issues concerning discipline in the language class will be discussed. Second, the original project I developed in 1995 to minimize the negative class participation of 14 EFL beginner students, aged 12-15, will be reviewed. Next, the experiment with the 2003 group will be described. The results seem to confirm that, although some adaptations to the original project were necessary, when students reflect upon their importance in the lessons, they tend to behave better in class and to show a more positive attitude towards learning. Key words: Classroom management, discipline, awareness-raising activities Este artículo discute los resultados de una investigación acción realizada para minimizar los problemas de disciplina en una clase de 10 alumnos de inglés, de nivel pre-intermedio, con edades entre 11-14 años, en un instituto de Rio de Janeiro, Brasil. En primer lugar, se discuten algunos presupuestos teóricos; en segundo lugar, presento el proyecto original que desarrollé en 1995 para trabajar con la indisciplina en mi clase de 14 alumnos principiantes en inglés, con edad entre 12-15 años. A continuación, se describe el experimento realizado con el grupo de 2003. Los resultados parecen confirmar que, aunque fueron necesarias algunas adaptaciones al proyecto inicial, cuando los alumnos reflexionan sobre su importancia para las clases, tienden a portarse mejor y demuestran una actitud más positiva hacia el aprendizaje. Palabras clave: Manejo del aula, disciplina, tareas de concientización